Digital Marketing Trends in Digital Entrepreneurship Education: A Literature Analysis of Opportunities and Challenges - Purwianti, Ari; Emilia Nur Cholifah; Sudarmiatin; Rizky Firmansyah (International journal of technology and education research, 2025)
Digitalization in entrepreneurship education has brought significant changes, especially with the integration of technologies such as Artificial Intelligence (AI), big data, and digital marketing. This research aims to analyze the main trends in digital marketing as well as the opportunities and challenges faced in the context of digital entrepreneurship education. The research method uses a qualitative literature study approach through thematic analysis of 9 relevant scientific articles. The results show that trends such as the use of AI and big data provide great opportunities for students to improve analytical competencies and business strategies. However, challenges remain, especially in terms of curriculum adaptation, faculty competence, and technological infrastructure. Strategies such as collaboration with industry, teacher training, and integration of technology in the learning process are needed for digital entrepreneurship education to produce competitive graduates in the era of globalization and digitalization